Effectiveness of Aspartame on Insulin, Triglycerides, and Blood Glucose Concentration in Adult Type 2 Diabetic Patients - Ali Deeb, Ammar S.; Al-Qudah, Maisa Muhammad Amin; Abu-Harirah, Hashem Ahmad; El-Qudah, Jafar Muhammad.; Abdelrahim, Dana; Altaleb, Hala Mashhour; Shoubaki, Lana Salman (Current Nutrition & Food Science, 2024)
Background: Human beings have an attraction to sweet items: desserts, fruits, honey, etc., which stimulate the sense of taste. However, sweet things tend to have many calories, thus contributing to issues with obesity. Moreover, those with diabetes must strictly limit their consumption of sugar to maintain their blood glucose levels within acceptable limits. Artificial sweeteners contain substances from several distinct chemical classes. The effects of artificial sweeteners on clinically relevant outcomes such as insulin, blood glucose, and lipids have been incompletely studied.Objective: This study aims to assess the effects of artificial sweeteners on blood glucose, triglycerides, and insulin in healthy, non-diabetic, and diabetic type 2 patients.Methods: Levels of glucose, triglycerides, and insulin in serum samples from 25 patients with confirmed Diabetic type 2 disease and 30 normal controls were determined at 30, and 60 after the ingestion of the drinks.Results: Levels of glucose, triglycerides, and insulin were notably higher in patients with diabetic Mellitus compared with the normal group. Both triglycerides and insulin (60 min) were elevated significantly above baseline after the intake of the artificial sweeteners in diabetic patients; however, values for all other conditions across time were very stable.Conclusion: There is no reason to suppose that a higher consumption would result in an elevation in these measures. Any noted insulin resistance linked to a high intake of artificial sweeteners is likely a function of the excess calories and processed ingredients often included within artificially sweetened food and beverage products.
Keywords: blood glucose